Can fast-twitch muscle fibres be selectively recruited during lengthening contractions? Review and applications to sport movements - Chalmers, G. R. (Sports Biomechanics, 2008)
Literature examining the recruitment order of motor units during lengthening (eccentric) contractions was reviewed to determine if fast-twitch motor units can be active while lower threshold slow-twitch motor units are not active. Studies utilizing surface electromyogram (EMG) amplitude, single motor unit activity, spike amplitude-frequency analyses, EMG power spectrum, mechanomyographic, and phosphocreatine-to-creatine ratio (PCr/Cr) techniques were reviewed. Only single motor unit and PCr/Cr data were found to be suitable to address the goals of this review. Nine of ten single motor unit studies, examining joint movement velocities up to 225% and forces up to 53% of a maximum voluntary contraction, found that the size principle of motor unit recruitment applied during lengthening contractions. Deviation from the size principle was demonstrated by one study examining movements within a small range of low velocities and modest forces, although other studies examining similar low forces and lengthening velocities reported size-ordered recruitment. The PCr/Cr data demonstrated the activation of all fibre types in lengthening maximal contractions. Most evidence indicates that for lengthening contractions of a wide range of efforts and speeds, fast-twitch muscle fibres cannot be selectively recruited without activity of the slow-twitch fibres of the same muscle.